HELPING LEARNERS TO DEVELOP READING SKILLS BY TEACHING A LESSON WITH PRE READING (Intent Research Scientific Journal, 2023)
Annotations in the form of explanatory notes, highlights, and underlines in the text can help learners identify key concepts, unfamiliar terms, and important ideas. This aids in active reading, promotes understanding, and encourages critical engagement with the material.